Seguro garantia em projetos de infraestrutura: uma perspectiva comparada entre mercados emergente e desenvolvido - Marques, Túlio Henrique Moreira (2020)
Infrastructure projects assume intensive capital usage and the participation of various actors, whereas institutional environment elements influence their respective contractual arrangements. Under a project governance perspective, risk transfer via surety bond (SB) is still little explored in research in Brazil. SB is a financial instrument with peculiar characteristics, with a social purpose to address a typical incompleteness of infrastructure markets, thus enabling social and economic development. Based on the Transaction Cost Theory (TCT), this work provides a qualitative investigation of risk mitigation in infrastructure projects through the SB in an emerging market (Brazil), having as reference a developed market (United States), through interviews in-depth with ten professionals from both countries and triangulated with secondary data obtained from lectures and debates on specific events in the insurance area. Results indicate that the high transaction costs present in the Brazilian market hinder the development of this risk hedging market, thus providing theoretical support to focused public policies. The academic contributions of the present study are: i) a broader qualitative understanding of large project markets and risk coverage dynamics through the TCT lens; ii) proposed filling of existing gaps for understanding the use of SB as a risk mitigation instrument; and iii) proposition of a theoretical framework for future efforts towards a much needed quantifying the intrinsic phenomena of using SB. As for the empirical contributions, we denote: i) indication of the adoption of governance instruments; and ii) indication for the development of public policies and contractual instruments to mitigate market failures.